Mechanism of herpesvirus UL24 protein regulating viral immune escape and virulence - Ruan, Peilin; Wang, Mingshu; Cheng, Anchun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Tian, Bin; Huang, Juan; Ou, Xumin; Gao, Qun; Sun, Di; et al. (Frontiers in Microbiology, 2023)
Herpesviruses have evolved a series of abilities involved in the process of host infection that are conducive to virus survival and adaptation to the host, such as immune escape, latent infection, and induction of programmed cell death for sustainable infection. The herpesvirus gene UL24 encodes a highly conserved core protein that plays an important role in effective viral infection. The UL24 protein can inhibit the innate immune response of the host by acting on multiple immune signaling pathways during virus infection, and it also plays a key role in the proliferation and pathogenicity of the virus in the later stage of infection. This article reviews the mechanism by which the UL24 protein mediates herpesvirus immune escape and its effects on viral proliferation and virulence by influencing syncytial formation, DNA damage and the cell cycle. Reviewing these studies will enhance our understanding of the pathogenesis of herpesvirus infection and provide evidence for new strategies to combat against viral infection.